Linear trend CALCULATING APPLICATION OF HOUSEHOLD ELECTRICITY USE WITH Least Square Method - Elly Agustina Julisawati (JAKSTIK Journal, 2004)
One to analyze the electricity consumption of households are using the calculation methodwith a Linear Trend Least square method. Linear trend values can be calculated the amountof electricity consumption for households with the formula:Yt = a + btWhere: Yt = total electricity consumption in KWHconstants a = b = coefficient t = year tThe value of a and b are first found using the least square method. After determining thevalue of a and b, the linear trend equation can yield how much per KWH of electricity useeach month.Based on the Value of Linear Trend, it is concluded fluctuations in electricity consumptiondarim every household, whether increased or decreased every month in a period. With so candikethui households which reflects the principle of saving in electricity usag